Detection of Human Papilloma Virus type 6 and type 11 in women with Breast Cancer by in situ hybridization technique. - Ismail, Noor H.; Al-Shammeri, Ahmed M.; Latif, Ayser H.; Majeed, Ayeda M.; Abed, Dina W. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Breast cancer is one of the common malignancies among women worldwide. Human papillomavirus (HPV) infections have been linked to many human cancers in addition to cervical cancer and one of them is breast cancer. Objective: To investigate the presence of human papilloma virus type 6 and type 11in breast cancer tissue specimens by in situ hybridization technique. Patients and Methods: Thirty four formalin-fixed, paraffin embedded tissue blocks from breast cancer patients were obtained from the archives of the pathology laboratory of Al-Yarmouk Teaching Hospital from January 2011 to July 2012. In addition formalin-fixed, paraffin embedded blocks tissue for twenty fibroadenoma of breast were collected and used as control group. In situ hybridization technique was used for the molecular detection of HPV type 6 and HPV type 11. Results: There were 82.4 % of breast cancer tissues positive for HPV type 6 and 88.2 % were positive for HPV type 11. Conclusion: The presence of human papillomavirus DNA in most breast carcinoma samples merits further investigation and confirmation by second assay in order to establish the exact role of this virus in the pathogenesis of breast cancer.